Wear Resistance and Longevity of Contemporary Dental Restorative Materials - Allayor ugli, Turayev Ismoil; Bustanovna, Islamova Nilufar (American Journal of Bioscience and Clinical Integrity, 2026)
The durability of dental restorative materials is critical for maintaining oral function, aesthetics, and patient satisfaction over time. Contemporary materials, including composite resins, glass ionomer cements, ceramics, resin-modified glass ionomers, hybrid ceramics, and high-strength polymers, offer diverse mechanical properties and wear resistance profiles suitable for posterior and anterior restorations. This study aims to evaluate the wear resistance, surface degradation, and long-term clinical performance of commonly used dental restorative materials under simulated masticatory conditions and in vivo follow-up. A total of 200 restorations were evaluated over a five-year period, including direct composite restorations, indirect CAD/CAM ceramic inlays/onlays, and glass ionomer restorations. Wear measurements were assessed using profilometry, digital imaging, and clinical evaluation scales, while longevity was recorded through survival analysis of restoration integrity, fracture, marginal adaptation, and secondary caries incidence. Results indicate that high-strength ceramics and hybrid CAD/CAM materials exhibit superior wear resistance and minimal surface degradation, maintaining functional and aesthetic integrity over time, whereas conventional composite resins demonstrate moderate wear, influenced by filler content, polymerization technique, and occlusal load. Glass ionomer-based materials display faster surface wear, especially under heavy occlusal stress, but offer fluoride release and ease of repair. Overall, material selection should balance mechanical performance, aesthetic requirements, and clinical handling characteristics to optimize long-term restoration success. This comprehensive evaluation highlights the importance of evidence-based material choice, patient-specific occlusal assessment, and regular monitoring to ensure longevity and functional outcomes.